ARCHAEOLOGICAL HISTORY OF CAGAYAN PROVINCE - Tobias, Carol M. (Hukay; Vol 2 No 1)
The scope of this paper includes an outline of the history of archaeology in Cagayan Province based on the reports and articles filed at the Records Section of the Philippine National Museum and some articles collated by the writer. This paper is limited to the archaeological history of Cagayan Province alone and not the whole Cagayan Valley Region (comprising Cagayan, Isabela, Quirino, and Nueva Vizcaya), although some works in these areas are mentioned. Covered in this article are the different archaeological activities done in the area and other related studies (such as geology, paleontology, zoology, etc.); the initial findings made from these studies; the people involved in these projects; and the laws that came out for the protection and regulation of these sites. This paper hopes to update researchers on the archaeological and related studies done in the Province. Also mentioned are the details of the initial discoveries made by farmers and other non-anthropologists before the second World War; the early studies and explorations done by American anthropologists in the area; to the involvement of the National Museum in search of the ‘Early Man’ in the 1970s; the participation of foreign archaeologists, geomorphologists and other experts in different fields; and the present archaeological activities. The research showed that archaeological activities were concentrated mainly in three areas: Solana, where fossil mammals were found; Peñablanca, where more than a hundred archaeological sites were determined from the more than two hundred fifty cave formations in the area; and Lallo, where large shell middens are located.